Congenital medulloblastoma in two brothers with SUFU-mutated Gorlin-Goltz syndrome: Case reports and literature review - Chen, Yufan; Zhang, Haibo; Zhao, Yang; Ma, Jie (Frontiers in Oncology, 2022)
BACKGROUND: Congenital medulloblastoma is very rare, and many cases involve germline mutations that can lead to inherited syndromes. Here, we first report two brothers with congenital medulloblastoma who were diagnosed with Gorlin-Goltz syndrome caused by SUFU mutation. CLINICAL PRESENTATION: Medulloblastoma was detected in two brothers at 2 and 3 months of age, with very similar imaging features. Genetic testing revealed that both children and their mother carried SUFU gene germline mutations, and both brothers were diagnosed with Gorlin-Goltz syndrome. CONCLUSION: Gorlin-Goltz syndrome-associated congenital medulloblastoma with SUFU germline mutation is very rare. Pathological types mostly involve desmoplastic/nodular or extensive nodularity; chemotherapy is the main treatment, and studies revealing prognostic data are scarce.